Principles of advocacy activity in proceeding in administrativeoffence cases - Puzyrnyi, Viacheslav (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
In the article, principles of advocacy activity in proceeding in administrative offence cases are investigated. Kinds of principles of advocacy activity in proceeding in administrative offence cases are characterised. Data concerning problems of realisation of principles of advocacy activity are displayed during performance by a lawyer of professional duties in proceeding in administrative offence cases.